Examined study of the impact of ethanol extract from Sirih China (Peperomia pellucida L.) ointment on the histological appearance of the epidermis and the duration of burn healing in mice (Mus musculus) - Harahap, Armansyah Maulana; Salamah, Salamah; Rambe, Robiatun; Elanda, Yurike; Khairunnisa, Nur Aini; Priawan, Indra (Program Studi Pendidikan Biologi, 2025)
Burns are a condition where there is damage to the epidermis layer down to the dermis layer. The skin structure sustains damage from the epithelium to the basal layer of the dermis. You can use the herbal Chinese pepper (Peperomia pellucida L.) for burn treatment. This study aims to evaluate the impact of administering Chinese betel leaf ointment, with variations in concentration and formula, on the duration of burn wound healing and the diameter of wound closure. Methods There were 30 Mus musculus mice in this study. Divided them into five groups: a regular group without burns, a positive control group that received gentamicin, treatment group 1 that received a low concentration 5% ethanol extract of Chinese betel leaf (EECB) ointment, a treatment group 2 that received a low concentration 10% EECB ointment, and a treatment group 3 that received a high concentration 15% EECB ointment. Results demonstrate wound closure activity by measuring the diameter of burn wounds treated with a 15% concentration of Chinese pepper ointment on the 18th day and a 15% concentration closed the burn wound. Histopathological differences were seen in the K3 group, where collagen density scored +3 (±0.06). We found a very weak positive correlation (0.000) between histopathology (collagen) and wound diameter and a strong negative correlation (-0.0527) between the histopathological parameter (collagen) and the duration of burn wound healing. Conclusion. The research concludes that the effectiveness of administering Chinese betel leaf ointment with a concentration of 15% was obtained